Measuring the Carnation Revolution: A Synthetic Control Analysis of Economic Crisis in Portugal (1974-1992) - Amaral, Luciano (2022)
On 25 April 1974, a military coup toppled Western Europe’s oldest dictatorship, Portugal’s Estado Novo. The following years were characterized by political and economic instability with a wage explosion and the reduction of working hours for the country’s labor force, the expropriation of the assets of the business elite and a process of capital flight, and the end of colonial trade and the arrival of about half a million repatriates with the end of the empire. As a result of these events the Portuguese economy slowed from its 1950s and ‘60s high growth and industrialization, when it had been counted among the fastest growing in the world. But measuring the impact of the “Carnation Revolution” is very difficult due to its coincidence with the 1970s oil shocks. What part of responsibility for the poor performance should be attributed to the international crisis and what part to the consequences associated with the revolution? To disentangle the problem, we use the synthetic control method with data for other OECD countries. We find that the Carnation Revolution and the subsequent events caused a negative structural break that made GDP per capita lower than it would have been in the absence of the revolution and the instability. We also analyze the effects on the current account and capital-labor ratios.